The Automobile Industry since 1945 - White, Lawrence J. (Cambridge : Harvard University Press, 1971)
The book is a study of the automobile industry and its behavior and performance in the postwar period, 1946 through 1967.
Includes index
rpm 22/01/2019
Loans
Keywords: Automobile Industry